The Influence of Health Logistics Management on the Nutritional Status of Vulnerable Groups in Post-Disaster Evacuation Locations - Andrafikar (CV. Get Press Indonesia, 2026)
Disaster situations often disrupt food supply chains and health services, increasing the risk of malnutrition among vulnerable populations in evacuation shelters. Effective health logistics management is therefore essential to ensure the availability, quality, and timely distribution of nutritional assistance during emergencies. However, empirical evidence linking logistics performance with nutritional outcomes remains limited. This study aimed to examine the influence of health logistics management on the nutritional status of vulnerable groups in disaster evacuation settings. A quantitative analytic approach with a cross-sectional design was applied. Data were collected in 2025 from 240 respondents representing vulnerable groups, including children under five, pregnant and breastfeeding women, older adults, and persons with disabilities. Samples were selected using proportionate stratified random sampling. Data collection involved structured questionnaires on logistics management, observation of distribution processes, and anthropometric and hemoglobin measurements to assess nutritional status. Data were analyzed using descriptive statistics, chi-square tests, and multivariate logistic regression with a significance level of 0.05. The results showed that most logistics indicators were categorized as adequate (52–62%), although gaps persisted in distribution timeliness and the quality of nutritional assistance. The prevalence of wasting, stunting, and anemia was 29.1%, 32.7%, and 37.4%, respectively. Delayed logistics distribution was significantly associated with wasting (AOR=2.34; p=0.005), while low-quality nutritional assistance increased the risk of anemia (PR=1.78; p=0.012). Strengthening logistics systems and improving aid quality are essential to reduce malnutrition.